The synthesis of phenanthroline and bipyridine based ligand for the preparation of Fe-Nx/C type electrocatalyst for oxygen reduction. (29th November 2018) - Chu, Ya; Gu, Lin; Du, Hongmei; Qu, Konggang; Zhang, Yan; Zhao, Jinsheng; Xie, Yu
Abstract: In this study, we synthesized a nitrogen rich compound (FPPHA) as the precursor of oxygen reduction reaction (ORR) catalysts, which was prepared based on 1, 10-phenanthroline-5-amine and 2, 2'-bipyridyl-5, 5'-dialdehyde. The FPPHA-Fe complex was formed and be loaded on the carbon powder to form the FPPHA-Fe/C composite catalyst. The pyrolysis of the FPPHA-Fe/C composite was conducted at different temperatures, including 700 °C, 800 °C, and 900 °C, and the resultant pyrolyzed materials were designated to FPPHA-Fe/C-700, FPPHA-Fe/C-800, FPPHA-Fe/C-900, respectively. The physical characteristics of the catalysts were examined by powder X-ray diffraction (PXRD), Brunauer–Emmett–Teller analysis, X-ray photoelectron spectrometer (XPS) and scanning electron microscopy (SEM) etc. The ORR performance of the composite catalysts were evaluated by cyclic voltammetry (CV), linear sweep voltammetry (LSV), and rotating ring disk electrodes (RRDE) in an alkaline solution. The results suggested that the pyrolysis process has a positive effect on the ORR activity of the catalysts, and among the catalysts the Fe-FPPHA/C-800 had the most preferable performance, which reduces oxygen through a predominantly four electron pathway with an average electron transfer number of 3.86 and an average hydrogen peroxide yield of 6.7%. Graphical abstract: Highlights: A N-containing ligand (FPPHA) was prepared based on phenanthroline and bipyridine. The complex Fe-FPPHA was prepared and be loaded on carbon powder as ORR catalyst. The Fe-FPPHA/C-800 was obtained through the pyrolysis of the Fe-FPPHA/C catalyst. The ORR performance of the catalyst could be improved through the pyrolysis process. Maximum power density of PEMFC achieved 0.078 W cm −2 at 50 °C without backpressure.